2015
DOI: 10.3389/fmed.2015.00085
|View full text |Cite
|
Sign up to set email alerts
|

Inflamma-miRs in Aging and Breast Cancer: Are They Reliable Players?

Abstract: Human aging is characterized by chronic low-grade inflammation known as “inflammaging.” Persistent low-level inflammation also plays a key role in all stages of breast cancer since “inflammaging” is the potential link between cancer and aging through NF-kB pathways highly influenced by specific miRs. Micro-RNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression at a posttranscriptional level. Inflamma-miRs have been implicated in the regulation of immune and inflammatory responses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 113 publications
0
14
0
Order By: Relevance
“…The influence of miRNA in microglia-mediated immune response was recently reviewed [83] and abnormal expression of inflamma-miRs showed them to contribute to chronic proinflammatory status and to be a significant mortality risk factor [84]. MiRNAs are small noncoding RNA molecules that are 18–25 nucleotides in length involved in the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of miRNA in microglia-mediated immune response was recently reviewed [83] and abnormal expression of inflamma-miRs showed them to contribute to chronic proinflammatory status and to be a significant mortality risk factor [84]. MiRNAs are small noncoding RNA molecules that are 18–25 nucleotides in length involved in the regulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Some aDNAm’s were identified in genes for non-coding RNAs (ncRNAs) that may affect regulation of gene expression [ 25 , 26 ] and involved in breast cancer [ 27 , 28 ]. It has previously been reported that ncRNAs may be associated with aging [ 29 ]., 8 aDNAm’s were located in the promoters of precursor-miRNAs (pre-miRNAs), indicating a possible regulatory role of the aDNAm’s in miRNA expression. These include mir-15b/16–2 that targets the BCL2 oncogene [ 30 32 ]; mir-7-3, a let-7 family member that regulates the RAS oncogene [ 33 ]; mir-148a, known to induce apoptosis by targeting IGF-1R and IRS1 in breast cancer cells [ 34 ]; mir-426 known to promote cell proliferation in breast cancer [ 35 ]; and, mir-935 known to be differentially expressed in hormone-responsive breast cancer cells [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In malignant diseases, the imbalance between overactivation of proto-oncogenes and inhibition of tumor suppressor genes is usually the consequence of a faulty regulatory system, which includes, among others, the non-coding RNAs (3)(4)(5). Most of these transcripts do not have the ability to interact with the ribosome and are not translated into proteins (6)(7)(8)(9)(10)(11); however, they interact with other coding or non-coding RNAs (ncRNAs), being part of complex regulatory networks (12). The ncRNAs are divided into two classes: the small ncRNAs (with <200 nt) and the long ncRNAs (lncRNAs), with >200 nt (13).…”
Section: Introductionmentioning
confidence: 99%